Short communication: Pattern of chlorophylls content declined during partial submergence for rice varieties cultivated in North Sulawesi at the vegetative stage - SONG AI NIO; DANIEL PETER MANTILEN LUDONG; RATNA SIAHAAN (Society for Indonesian Biodiversity, 2022)
Abstract. Nio SA, Ludong DPM, Siahaan R. 2022. Short communication: Pattern of chlorophylls content declined during partial submergence for rice varieties cultivated in North Sulawesi at the vegetative stage. Biodiversitas 23: 2451-2456. Submergence or flooding stress limits plant growth in various physiological, anatomical, and morphological aspects. This study examined leaf chlorophyll content as a physiological response in some rice varieties cultivated in North Sulawesi during partial submergence imposed at the vegetative stage. Ten rice cultivars, i.e., Permata, Superwin, Cigeulis, Pulo Manado, TB, Ombong, Serayu, Temo, Burungan, and Inpari 31, were grown in plastic trays on planting media in the greenhouse, then watered to field capacity using a mixture of water and fertilizer every second day for two weeks. The plants were submerged 18 cm from the media's surface, and the content of leaf chlorophylls (total chlorophyll, chlorophyll a, and chlorophyll b) were measured using a spectrophotometer (? 649 and 665 nm) at 0, 3, 6 and 9 days of partial submergence. The chlorophylls (total, a, and b) content decreased during the 9 days of treatment. The highest chlorophylls contents were observed in rice cv. Superwin and the chlorophylls content at day 0 (before partial submergence commenced) were higher than at 3, 6, and 9 days after treatment (p<0.05). The data presented here supported that leaf chlorophylls content is a potential physiological indicator of partial submergence stress in rice, including the North Sulawesi local rice, at the vegetative phase.